Energetic particle optimization of quasi-axisymmetric stellarator equilibria - Alexandra LeViness; John C. Schmitt; Samuel A. Lazerson; Aaron Bader; Benjamin J. Faber; Kenneth C. Hammond; David A. Gates (Nuclear Fusion, 2022)
An important goal of stellarator optimization is to achieve good confinement of energetic particles such as, in the case of a reactor, alphas created by deuterium–tritium fusion. In this work, a fixed-boundary stellarator equilibrium was re-optimized for energetic particle confinement via a two-step process: first, by minimizing deviations from quasi-axisymmetry (QA) on a single flux surface near the mid-radius, and secondly by maintaining this improved QA while minimizing the analytical quantity $Γ_C$ , which represents the angle between magnetic flux surfaces and contours of $J_{||}$ , the second adiabatic invariant. This was performed multiple times, resulting in a group of equilibria with significantly reduced energetic particle losses, as evaluated by Monte Carlo simulations of alpha particles in scaled-up versions of the equilibria. This is the first time that energetic particle losses in a QA stellarator have successfully been reduced by optimizing $Γ_C$ . The relationship between energetic particle losses and metrics such as QA error ( $E_qa$ ) and $Γ_C$ in this set of equilibria were examined via statistical methods and a nearly linear relationship between volume-averaged $Γ_C$ and prompt particle losses was found.